The Online Learning Challenges of EFL Students In San Pedro University During The Covid-19 Pandemic - Yusniaty Lodo, Rozita; Ajito, Timoteus (Lingustic, Literature and English Education, 2022)
The spread of Covid-19 in Indonesia has an impact on the country's educational system. Face-to-face instruction is being replaced by full-fledged online learning from the comfort of one's own home. This study was conducted to determine the challenges of online learning on EFL students. A qualitative method was applied in this study. The data for this study was gathered through interviews and documentation. EFL students from the English education department at Universitas San Pedro in the first semester were the focus of this study. The findings of this study revealed that students faced a variety of challenges while learning online, including internet data, internet connection, difficulty completing assignments, intrusion, a lack of prior experience with technology, comprehension of EFL lessons, and interaction between students and lecturers. On the other hand, students have reported feelings of dissatisfaction and unhappiness as a result of their online learning.